2018
DOI: 10.1007/s00455-018-9892-9
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Dysphagia Evaluation Tools in Adults with Solid Malignancies Outside the Head and Neck and Upper GI Tract: A Systematic Review

Abstract: Dysphagia is often associated with head and neck and upper gastrointestinal (GI) tract cancers. Evidence suggests that those with solid malignancies in other primary sites may also have swallowing difficulties. Timely and accurate identification of dysphagia is important given the impact it has on hydration, medical treatment, nutrition, prognosis, and quality of life. A systematic review was conducted to identify swallow screening, evaluation, and quality of life tools for those with solid malignancies outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 105 publications
3
11
0
1
Order By: Relevance
“…These are quick to administer, nonburdensome for participants, and based on best available evidence. 74…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are quick to administer, nonburdensome for participants, and based on best available evidence. 74…”
Section: Discussionmentioning
confidence: 99%
“…This was adapted from another study, 73 which was found to be a good dysphagia screen. 74 A question about chewing difficulties was added because dysphagia diagnosis includes masticatory difficulties. A third about ''being more aware of your swallow'' was added in case dysphagia was subclinical.…”
Section: Screeningmentioning
confidence: 99%
“…Dysphagia is the difficulty in swallowing in initial phases (oropharyngeal dysphagia) or the obstruction sensation when the solids and liquids are moving from the mouth to the stomach (esophageal dysphagia). The groups of people most affected are the elderly people, more than 50% of institutionalized elderly population, [1] as well as 60-75% of the patients who undergo radiotherapy for head and neck cancer, [2] and up to 80% of people with neurodegenerative diseases. [3] In some hospitals or geriatrics, 75% of elderly people have nutritionals problems because the oropharyngeal dysphagia is not correctly diagnosed or the diet is not fit for their requirements.…”
Section: Introductionmentioning
confidence: 99%
“…En la Tabla 2, se presenta los tipos de artículos que se seleccionaron que fueron 3 como son descriptivos, analíticos y experimentales en el rango de las fechas de publicación de los artículos y las cantidades obtenidas en total, se realiza un agregado de los autores que se tuvieron en cuenta con más de una publicación pero que fuera un estudio totalmente diferente. El rol que enfrenta el enfermero en este campo aun no es claro y tiene el reto de identificar su rol en un equipo interdisciplinar y ser partícipe del control de los síntomas, asegurándose de las necesidades individuales, concretas y específicas en continuo cambio y evolución del paciente y su familia, fomentando la autonomía y los derechos de la persona y ofrecer acompañamiento, respetando sus valores, creencias y estilos de vida, siempre en pro del confort, bienestar y calidad de vida 58 .…”
Section: Vol 10 Nº 1 Enero -Abril 2019 Bucaramanga Colombiaunclassified